2011
DOI: 10.1016/j.jvs.2011.06.025
|View full text |Cite
|
Sign up to set email alerts
|

The results of a simplified technique for safe carotid stenting in the elderly

Abstract: The results of this preliminary study indicate that the transcervical approach with flow reversal during the insertion of the protecting filter allows CAS with minimal interruption of cerebral circulation and is simple and safe in patients unsuitable for CEA and transfemoral CAS for anatomic reasons. Further research with randomization and with pre-procedure and post-procedure diffusion-weighted magnetic resonance imaging (DW-MRI) is required in order to expand the indications of this method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…The system's design allows the circuit to drape down the patient's thorax and abdomen and allows a single interventionist to work between midchest and midabdomen away from the X ray source and image intensifier. 36 The second variation, described by Christopoulos et al, 23 implies only cannulation of the CCA and establishes retrograde flow toward a blood transfusion bag positioned as low as possible so that the pressure gradient ensures reverse ICA flow. The patients can be autotransfused after the procedure.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The system's design allows the circuit to drape down the patient's thorax and abdomen and allows a single interventionist to work between midchest and midabdomen away from the X ray source and image intensifier. 36 The second variation, described by Christopoulos et al, 23 implies only cannulation of the CCA and establishes retrograde flow toward a blood transfusion bag positioned as low as possible so that the pressure gradient ensures reverse ICA flow. The patients can be autotransfused after the procedure.…”
Section: Resultsmentioning
confidence: 99%
“…12,13 Of the remaining 23 publications, 17 were from the same author or institution. [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] The study that was most recent or that reported the largest number of patients was included in the analysis. 17,19,21,23,25,30 Twelve articles were considered.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is a safe and useful technique by which consistent hemostasis is possible regardless of the thickness of the sheath used or whether or not heparin is used. 6,[11][12][13][14][15][16][17][18][19] Demerits of the technique are complications associated with general anesthesia and prolongation of the surgical time. However, the merit of avoidance of the risk of puncture troubles and postoperative hematoma formation is significant, warranting the preparation of an environment capable of handling cervical incision under general anesthesia.…”
Section: Disclosure Statementmentioning
confidence: 99%